"The person with maximum knowledge will win the race": Conceptualizing knowledge in microbusinesses. (4th March 2023) - Haq, Muhibul; Davies, Julie
ABSTRACT: The concept of knowledge and the process of knowledge sharing in ethnic minority microbusinesses remain neglected in contemporary debates even if their role for economic development is recognized. Drawing on a culturalist view, we explore how knowledge is defined and shared in a local niche market. Thematic analysis of semistructured qualitative interviews with 32 owner-managers and 11 employee-managers reveals that, contrary to studies on larger firms, local knowledge creation and sharing narrowly based on ethnic strengths are valuable sources of competitive advantage. Our study has implications for researchers, policymakers, and practitioners in exploring, supporting, and integrating ethnic minority microbusinesses.